Increasing Trends, Late Presentation and Challenges of Colorectal Cancer in Uganda - Wismayer, Richard; Kiwanuka, Julius; Wabinga, Henry; Odida, Michael (Research Developments in Medicine and Medical Science Vol. 3, 2023)
Introduction: In Uganda, a trend towards an increased incidence of colorectal cancer (CRC) has been observed. According to the Kampala Cancer Registry, there has been a 4.1% annual percentage increase in the incidence of CRC among female patients. These patients present mainly with late-stage disease with resultant high morbidity and mortality. The aim of our study was to document the burden of CRC, late-stage presentation and challenges associated with the increase CRC in Uganda. Methods: A cross-sectional study was carried out between 2008 and 2021 on 404 patients with histologically diagnosed colorectal adenocarcinoma in central Uganda. Clinical records were reviewed, and data were extracted for date of diagnosis, age, sex, location of the primary tumour, type of operation and TNM stage. Among 128 CRC patients recruited and followed up, we obtained data on whether they had a colonoscopy and whether there were colorectal adenomas. Results: The median age was 54(43-67) years, with 38.9% being \(\le\)49 years of age. The male: female sex ratio was 1:1, and advanced-stage disease constituted 217(60.8%) CRC cases. In all age groups, the frequency of CRC increased from 17 cases in 2008 to 61 cases in 2021. Out of the 128 participants who were followed up prospectively, only 56(43.8%) had a colonoscopy, among whom 5(8.9%) CRC patients had colorectal adenomas. Having a family history of CRC (OR=19.83, 95% CI: 2.56-153.74, p=0.004) and GI cancers (OR=6.79, 95% CI, 1.02-45.08, p=0.047) were associated with having colorectal adenomatous polyps. Rectal tumours were the most common tumours 212(53%), whereas the most common operation performed was a low anterior resection among these CRC patients 81(30%). Conclusions: The increase in the CRC burden in Uganda should be made a public health priority. Increasing the endoscopic and surgical infrastructure to improve the ability to screen, diagnose and manage CRC is important to improve morbidity and mortality. The high number of young individuals diagnosed with CRC is of concern. Therefore, age-appropriate national screening guidelines and education campaigns are necessary for Uganda to manage the increasing burden of CRC.